Comunicação e cidade: o habitar como inveção - Santos, Adriana Maciel Gurgel (2014)
The empirical object of this work is the city of São Paulo, downtown São Paulo more specifically (marked by the Copan building, designed in the 1950s by Oscar Niemeyer), and the Hansaviertel neighborhood in Berlin, Germany (rebuilt at the end of the 1950s based on the premisses of the Modern Movement). This thesis proposes to investigate the conflict between the programmed space (which was designed rationally in accordance to the Modern Movement principles) and the living experience of the city, delineated by everyday life and its expressions. Such investigation will take advantage of the observation and analysis of mediating and interactive processes, or those situated between mediation and interaction. The conflict between the designed reality and the one effectively experienced can be methodologically observed through random movements instructed by expressions of communication. Such analysis focuses on the visual characteristics that communicate distinct living models and that go beyond mere descriptive and analytical phenomena. In sum, this thesis proposes to investigate how the Modern ideals related to architectural design were experienced in everyday life, through the analysis of images obtained both in Sao Paulo (at the Copan) and Berlin (at the Niemeyer-Haus, the building designed by Niemeyer in Hansaviertel). These images, taken as signs of visualities and visibilities, are the product of the life of the inhabitants of these buildings, who transform the original designs and reinvent the space through everyday life. The basic hypothesis is that these transformations promote an endless renovation of urban communication, thus making it possible to know the city by understanding living as a cultural act. The authors and concepts that are relevant to this analysis concern: the relationship between the designed space and the experienced city, and the notions of visuality and visibility developed by Lucrécia Ferrara; the characterization of the everyday living and its expressions described in the work of Michel de Certeau, Milton Santos and Jane Jacobs; the dialogue between living and inhabiting as invention/transcreation (Haroldo de Campos e Julio Plaza); and finally the semiotic horizon of C. S. Peirce, that guided the development of this research